THE RELATIONSHIP BETWEEN ENTREPRENEURIAL COMPETENCE, SOCIAL COMPETENCE, AND MANAGERIAL COMPETENCE OF MADRASAH PRINCIPALS AND STRATEGIC DECISIONS IN MANAGING EDUCATIONAL RESOURCES AT STATE MADRASAH ALIYAH IN RIAU ISLANDS PROVINCE - Deassy Arestya Saksitha Pulungan; Risnita Risnita; Kemas Imron Rosadi; Asrulla Asrulla (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to examine the correlation between Entrepreneurial Competence, Social Competence, and Managerial Competence with Strategic Decisions. The usefulness of this research is to enrich the scientific paradigm in the field of Islamic Education Management, particularly in the study of Human Resource Management. This research is a quantitative study using a survey method. The research population includes all academic communities in State Madrasah Aliyah in Riau Islands Province. The sample consisted of 155 respondents, selected through purposive sampling techniques. A questionnaire with a Likert scale was used as the instrument. Data were analyzed using correlation analysis. The results show that: (1) Entrepreneurial Competence (X1) has a direct influence on Strategic Decisions (Y) by 27%. (2) Social Competence (X2) has a direct influence on Strategic Decisions (Y) by 30%. (3) Managerial Competence (X3) has a direct influence on Strategic Decisions (Y) by 44%. (4) Entrepreneurial Competence (X1), Social Competence (X2), and Managerial Competence (X3), simultaneously, have a direct influence on Strategic Decisions (Y) by 48%. The conclusion of this study is that Entrepreneurial Competence, Social Competence, and Managerial Competence can influence Strategic Decisions. Strategic decisions are a crucial element in determining the direction and sustainability of an organization. This research proves that several factors can influence strategic decision-making, including entrepreneurial competence, social competence, and managerial competence.